The Influence of Flash Sales and Free Shipping on Shopee on Impulsive Buying Among Gen Z in Nganjuk Regency - Wijianto, Hafid Syahromi; Djunaidi, Djunaidi; Rahmadi, Afif Nur (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2024)
This study aims to examine the influence of flash sales and free shipping vouchers on impulsive buying on Shopee among Generation Z in Nganjuk Regency. The background of this research is the high online shopping activity among Generation Z, which is influenced by e-commerce promotions. This study uses a quantitative design with a survey method. The subjects of the research are Generation Z in Nganjuk Regency who have an income and frequently use the Shopee application. The data collection instrument is a questionnaire distributed online via Google Forms. Data analysis techniques include validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis conducted with SPSS 25. The results of the study show that flash sales and free shipping vouchers have a significant influence on impulsive buying. The conclusion of this research is that promotional strategies such as flash sales and free shipping vouchers can increase impulsive purchases among Generation Z. This study provides insights for e-commerce businesses in designing effective marketing strategies to attract young consumers. Keywords:Flash Sale, Free Shipping, and Impulse Buying.